The association of plasma high-density lipoprotein cholesterol levels and cirrhosis development in obese patients with chronic hepatitis B: a cohort study. Issue 5 (16th October 2020) - Wang, Xian; Chen, Hui-Zhen; Liu, Wan-Ting; Liu, Min; Zhou, Dong-Qi; Chen, Qiu; Peng, Bo
Abstract : Objective: Metabolic disorder is a common risk factor for cirrhosis in Asia, and it will increase the risk of cirrhosis in patients with Chronic hepatitis B (CHB). However, studies on the efficacy of plasma lipid markers which predict the happening and development of cirrhosis in obese CHB patients are limited. Methods: In total, 3327 patients who were followed for more than 4 years' follow-up in the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine joined the program. Finally, 287 obese CHB patients were included in this study according to the results of metabolic tests. The data of baseline and follow-up were collected, and the association between them was analyzed. Results: Based on the follow-up results, enrolled patients were divided into a group of cirrhosis ( n  = 146) and a group of noncirrhosis ( n  = 141). Plasma glucose and high-density lipoprotein cholesterol (HDL-C) levels in the noncirrhosis group (5.2 and 1.2 mmol/L, respectively) were significantly higher than that in the cirrhosis group (5.0 and 1.0 mmol/L, respectively), while the amount of total bile acid (TBA) in the cirrhosis group was lower than that in the cirrhosis group. Levels of HDL-C and total cholesterol were associated with liver function. Plasma HDL-C was an independent indicator of cirrhosis in patients with CHB. Patients with HDL-C levels less than 1.03 mmol/L had a 2.21-fold higher incidence rate of cirrhosis, and patients over 40 years old or the levels of HDL-C less than 1.03 mmol/L were more likely to generate cirrhosis. Conclusions: Plasma HDL-C was an appropriate marker in predicting cirrhosis for patients with CHB.